Social determinants of emotional well-being in new refugees in the UK - Campbell, M. R. (Public health, 2018)
Objectives: Refugees are most vulnerable to mental health problems of all migrant groups, and an understanding of the role of postdisplacement social factors in refugee emotional well-being can help to shape the future interventions for this group. We aimed to investigate the effect of social determinants, such as employment, language ability and accommodation, on mental health in refugees in the UK. Study design: This prospective longitudinal cohort study was set in the UK. The study population of new UK refugees was drawn from an existing data set of the Longitudinal Survey of New Refugees (n = 5678), in which all new UK refugees (2005-2007) were sent a postal questionnaire at four time points across 2 years. Methods: Ordered logistic regression models were used to evaluate associations between social determinants and the dependent variables, emotional well-being or change in emotional well-being, using a question from the Short Form-36 Health Survey Questionnaire. Results: Refugees who were unemployed in the UK, could not speak English well or were unsatisfied with their accommodation had significantly higher odds of poorer emotional well-being in the cross-sectional analysis (P < 0.05 at all time points measured). Conclusions: Postdisplacement social factors, including language ability, employment status and accommodation satisfaction, were important determinants of refugee emotional well-being. Changes in these social determinants have the potential to improve refugee mental health, making them legitimate, modifiable targets for important public health interventions. Accounting for this, further research into how to improve refugee well-being is crucial given the increase in refugee numbers around the developed world.